PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN MOTIVASI BELAJAR MATA PELAJARAN PAI DI SD N 2 GONDANG, PURWANTORO - Huda, Muhammad Fatchul; Masyuri, Masyuri; Mualim, Rojif (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2024)
This type of research is qualitative research with a descriptive approach. The data sources used in this research include the main source in the form of interviews with the Principal, Islamic Religious Education Teacher, and students from SD N 2 Gondang Purwantoro, as well as additional sources in the form of photos of activities. Data collection was carried out through a process of interviews, observation and documentation. The results of this research show that: The strategy implemented by Islamic Religious Education teachers in increasing PAI learning motivation at SD N 2 Gondang Purwantoro involves several actions, such as familiarizing themselves in the school environment, being a good example for students, collaborating with fellow teachers, and involving students in the process of learning religion at school. Students' learning motivation towards PAI at SD N 2 Gondang Purwantoro has increased quite significantly. This can be seen from the large number of students' participation in learning, including asking questions during the learning process, completing assignments, the high level of student enthusiasm during study hours, and the habit of praying before and after lessons. There are factors that support and hinder efforts to increase students' learning motivation towards PAI at SD N 2 Gondang Purwantoro. Internal factors, namely factors that come from within the student, as well as external factors, which include the role of teachers, school principals, and supporting assistance, both influence this process.